Patient Reported Outcome Measures for Major Lower Limb Amputation Caused by Peripheral Artery Disease or Diabetes: A Systematic Review. (March 2021) - Miller, Rachael; Ambler, Graeme K.; Ramirez, Jozel; Rees, Jonathan; Hinchliffe, Robert; Twine, Christopher; Rudd, Sarah; Blazeby, Jane; Avery, Kerry
Abstract : Objective: Most major lower limb amputations are related to peripheral artery disease (PAD) or diabetes. Just 40% of patients who undergo major lower limb amputation will use a prosthesis yet measures of surgical success commonly focus on prosthesis use. Patient reported outcome measures (PROMs) are valuable to comprehensively evaluate health related quality of life (HRQL) after surgery. This systematic review aimed to identify and describe PROMs available to assess HRQL in patients after amputation for PAD or diabetes. Methods: A search was conducted based on the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) for systematic reviews of PROMs. Ovid MEDLINE, Ovid EMBASE, PsycINFO, CINAHL, and Cochrane CENTRAL were also searched from inception until August 2019. Included were articles describing the development, measurement properties, or evaluation of HRQL via a PROM in adult patients after amputation for PAD or diabetes. Studies of amputation exclusively for trauma or malignancy were excluded. Data were collected on study characteristics, PROM characteristics (generic/disease specific), and properties of amputation specific PROMs. Results: Of 3 317 abstracts screened, 111 full text articles were assessed for eligibility and 64 included. Fifty-six studies evaluated HRQL, with 23 (46%) of these using an amputation specific PROM to do so. Eleven different amputation specific PROMs were identified, 10 (91%) of which were developed only for prosthesis users. One measure was suitable for use in all patients after amputation. This "Amputee single item mobility measure" includes a single item evaluating mobility. Nine studies reported some psychometric testing of an amputation specific PROM. Conclusion: A well tested, multidimensional PROM applicable to wheelchair and prosthetic users after amputation is lacking and urgently needed for studies in this field. Future work to develop an appropriate measure is required.